Pembelajaran Kombinasi Menggunakan Konteks Tim Sepak Takraw - Rarri Bian Ryandi; Somakim Somakim; Ely Susanti (Universitas Sarjanawiyata Tamansiswa, 2018)
This study aims to produce a learning trajectory using takraw teams context in helping students to understand the concept of combinations. This research used design research to give in developing local instructional theory in learning combinations. Learning trajectory designed in the early phases and tested on 36 tenth-grade students in SMA N 15 Palembang. This result is a learning trajectoryÂ which consists of 3 activities using takraw teams context:1) student do role-play scene of selecting main teams and handshake between players, this supports students to understanding in combinations order doesnâ€™t matter. 2) students analyze the general pattern of combination with the knowledge of students about the factorial. 3) student solve problems related to combination helps students in thinking about how to solve a real-world problem related to combination. From the resulting activity can be concluded that learning to use takraw teams context can help students understand the concept of combinations.